GE_GERICHTE C/22524/2014 vom 11. September 2017 - GE Cour de justice (2017)
BAIL À FERME ; DÉFAUT DE LA CHOSE ; TRAVAUX D'ENTRETIEN(EN GÉNÉRAL) ; FRAIS DE RÉPARATION | CO.275; CO.259a; CO.279; CO.259d; CO.284;